The Interpretation of Hijab Verses in Q.S. Al-Ahzab and An-Nur: A Comparative Analysis of Tafsir Ibn Kathir and Tafsir Al-Misbah - Umar Ghifari; Solahudin S; Muhammad Thalib (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the interpretation of hijab verses in QS. Al-Ahzab [33]: 59 and QS. An-Nur [24]: 31 through a comparative analysis of Ibn Kathir’s Tafsir Al-Qur’an Al-‘Azhim and M. Quraish Shihab’s Tafsir Al-Misbah. The study is motivated by the diversity of interpretations concerning hijab, particularly regarding its meaning, forms of clothing, and underlying purposes. Such differences require examination through the works of exegetes who employ distinct interpretive characteristics and approaches. This study employs a qualitative method using library research with a descriptive-comparative approach. The primary data consist of QS. Al-Ahzab [33]: 59 and QS. An-Nur [24]: 31 and their interpretations in Ibn Kathir’s and Quraish Shihab’s exegetical works, while secondary data are obtained from relevant books, scholarly journal articles, and previous studies. Data were collected through the identification, documentation, and classification of relevant sources and were subsequently analyzed descriptively and comparatively to identify the similarities, differences, and interpretive characteristics of the two exegetes. This study is expected to contribute to a more comprehensive understanding of the Qur’anic verses concerning hijab and to demonstrate how differences in sources, methods, and interpretive contexts may influence the understanding of these verses.